The impact of public procurement on financial barriers to green innovation: Evidence from the European Community Innovation Survey - Dorothea Schäfer; Andreas Stephan; Sören Fuhrmeister (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
The purpose of this study is to identify whether an innovative company's likelihood of facing financial constraints is different when the company possesses a public procurement contract (PP). Theory suggests that the treatment effects of public procurement, particularly when mediated by the demand-pull effect, may lower a company's funding constraints for innovation. We test this theory and apply extended probit models (eprobit) with treatment and selection to control for an omitted variable bias. Our findings indicate that the treatment effect of PP on the likelihood of facing financial constraints is highly significant and positive. The increased prefunding requirements that usually come along with PP may actually overcompensate the possibly constraint-reducing effects from a demand-pull or certification effect of PP. The treatment effect of PP is particularly strong for internal financial constraints backing the notion, that PP increases the need for upfront funding.
Keywords: G30; O16; O31; Q56; 330; public procurement; green public procurement; financial constraints; green innovation; sustainable finance; small and medium-sized enterprises